Gender equality and social inclusion in landscape management: the case of Nyamasheke and Rusizi districts in Rwanda - Nigussie, Likimyelesh; Osei-Amponsah, Charity; Muhorakeye, L.; Uwanyirigira, D.; Tilahun, Seifu A.; Atampugre, Gerald; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
Gender Equality and Social Inclusion in agriculture and natural resource management is crucial for addressing climate change and land degradation. In Rwanda, laws and policies support gender equality and environmental sustainability. Despite efforts to involve both genders in decision-making, power dynamics persist, impacting landscape management priorities, knowledge valuation, resource rights, benefits distribution, and decision processes. This study investigates the interplay between gender and multiple identities, including marital status, socioeconomic status, and age, alongside power dynamics. It emphasizes how these factors affect rights to resources, the transfer of knowledge and skills, and the impact on participation in decision-making processes which are essential for effective landscape management in the Rubyiro Sub-Catchment located in Rwanda's Rusizi and Nyamasheke districts. It is a qualitative study based on data gathered in May and June 2024 using eight key informant interviews (four men and four women), 20 household interviews (ten men and ten women), and eight focus group discussions (four with men groups and four with women groups). The results suggest that the Government of Rwanda has put in place legal frameworks to advance environmental sustainability, gender equality, and sustainable development. However, the experiences of farmers, regardless of gender, highlight that age, gender, socio-economic conditions, and power relations significantly impact their rights to resources, their capacity to voice opinions, and their representation in landscape management, thereby affecting its effectiveness. The following are the three primary key results and recommendations.